CHANGES IN DUNG BEETLES ALONG AN ALTITUDINAL GRADIENT OF TROPICAL FORESTS IN PU HOAT NATURE RESERVE, NGHE AN PROVINCE - Van Bac, Bui; Dinh Duc, Bui (Journal of Forestry Science and Technology, 2022)
Dung beetles are widely used as bio-indicators of habitat changes because they respond quickly to changes in environmental conditions. Altitudinal variation in dung-beetle communities has been studied in various geographical areas. However, there is little known about dung-beetle shifting in tropical forests of Vietnam. This study investigates dung-beetle communities along an altitudinal gradient ranged from 400 to 800 m above sea level (a.s.l.). We collected dung beetles at three transects of three altitudinal classes (altitudinal class 1 = 400 m a.s.l., class 2 = 600 m a.s.l., and class 3 = 800 m a.s.l.) in primary forests of Pu Hoat Nature Reserve, using baited pitfall traps. In total, 28 dung-beetle species of 10 genera were recorded during the course of the study. Of the total recorded species, 25, 22 and 17 species were collected in the altitudinal class 1, class 2, and class 3, respectively. The ANOVA test and Tukey’s post-hoc test showed significant differences in species richness, Shannon diversity, and abundance of dung beetles across the altitudinal gradient. Altitudinal class 1 had the highest richness of dung beetles. However, the highest abundance was recorded in the altitudinal class 2. Several dung-beetle species, in response to global warming, have shifted their altitudinal range upward, leading to serious conservation problems such as extinctions of high-elevation species.